COMPARATIVE ECONOMICS AND CONSTRAINTS ANALYSIS OF COTTON GROWERS UNDER DIFFERENT FARMING SITUATIONS OF TELANGANA STATE - D. SRINIVASA REDDY and D. SRINIVASA CHARY, S. RADHA, K. SUHASINI, MD. ALIBABA (The Journal of Research, PJTSAU, 2023)
Cotton the ‘King of fibres’ is the important commercial crop of Telangana state occupying an area of 23.48 lakh hectares with 30.42 lakh MT of production during the year 2020-21. The crop is mainly grown under rainfed condition in a wide range of soilslike red loamy, deep black, chalka soil and dubba. Considering the different soil types and the irrigation availability, the costs andreturns were computed for different farming situations viz., FS-1 (Irrigated red soil), FS-2 (Rainfed red soil), FS-3 (Chalka soil), FS-4 (Irrigated black soil) and FS-5 (Rainfed black soil). Further, the constraints were analysed based on the primary data collectedfrom 350 cotton growing farmers from 16 villages belonging to eight mandals of districts viz., Nalgonda, Nagarkurnool, Adilabad and Sangareddy during the year 2020-21. The comparison done using tabular analysis inferred that, cotton cultivation was highlyprofitable in FS-4 with net returns of ( 64773.67) followed by FS-1 ( 48680.16), FS-5 ( 33483.70) and FS-2 ( 24441.86) while, in FS-3 it was a loss with negative net returns ( -1310.70). Economically unviable cotton cultivation in FS-3 recommends for cultivation of other suitable crop viz., millets, pulses and ground nut. Further, constraint analysis inferred that, the crop suffered from pests and diseases infestation, inadequate /excess rainfall, labour scarcity, lack of infrastructure leading to low prices at the time of harvest and poor technical know-how. Hence, the study recommends developing resistant cotton hybrids. Adoption of mulching practices in rainfed cotton, timely and adequate irrigation via water saving techniques in irrigated cotton, better infrastructure and training programmes for dissemination of new technologies is much needed.